Acute Total Bowel Obstruction Caused by Locally Advanced Rectal Carcinoma without Confirmed Distant Metastasis: A Case Report - Rizky Hardwiansyah; Begard Mada Sagaling; Sahrul Anam; Wisnu Widiyatmoko (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Rectal cancer may present with nonspecific symptoms that are frequently overlooked, leading to delayed diagnosis and advanced disease. Acute bowel obstruction is a severe complication associated with increased morbidity and emergency surgical management. A 49-year-old male presented with a three-day history of inability to defecate and pass flatus, accompanied by severe abdominal pain, distension, vomiting, and fever. He had a two-year history of an untreated anal mass, chronic constipation, rectal bleeding, and significant weight loss. Physical examination revealed a friable mass completely obstructing the anal canal. Imaging showed obstructive ileus and generalized peritonitis. Emergency exploratory laparotomy revealed a large, fixed tumor at the distal rectum with extensive bowel dilatation. Transverse colostomy and tumor debulking were performed. The postoperative diagnosis was rectal carcinoma staged intraoperatively as T4bN1Mx. This case demonstrates that severe local tumor progression may result in life-threatening obstruction even in the absence of confirmed distant metastasis at presentation. Diagnostic delay and emergency presentation significantly influence management strategy and outcomes. Rectal cancer can progress to total bowel obstruction due to extensive local disease. Early evaluation of chronic anorectal symptoms is crucial to avoid emergency presentations and associated complications.